South-Western training for organizations - O'Connor, Bridget N., 1952-; Bronner, Michael; Delaney, Chester (Cincinnati, Ohio : South-Western Educational, 1996)
This book is divided into six parts: The Training Function; Needs Assessment and Evaluation; Instructional Design; Trainning Delivery; Additional Job Skill for Trainers (Tools of the Trade); and Trends for the Future.
Keywords: Training; Employees; Organization; Employees -- Training of